2013
DOI: 10.1158/0008-5472.sabcs13-s5-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S5-06: Epirubicin and cyclophosphamide (EC) followed by paclitaxel (T) versus fluorouracil, epirubicin and cyclophosphamide (FEC) followed by T, all given every 3 weeks or 2 weeks, in node-positive early breast cancer (BC) patients (pts). Final results of the gruppo Italiano mammella (GIM)-2 randomized phase III study

Abstract: Background. Using a 2 × 2 factorial design, we compared the efficacy of two different schedules of chemotherapy (CT), dose-dense (DD) every 2 weeks versus standard duration every 3 weeks and the role of Fluorouracil (F) in addition to EC, in the adjuvant treatment of node positive BC pts. Patients and Methods. Node positive early BC pts younger than 70 years were eligible and randomly assigned to one of the following treatment arms: ARM A (4 courses of EC [90/600 mg/m2, on day 1, q 21] followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Based on data from the Italian Grupo Italiano Mamella (GIM) study presented by Cognetti et al [76] at the San Antonio Breast Cancer Symposium (SABCS) 2013, epi rubi cin/cyclophosphamide (EC) followed by paclitaxel is equally effective to EC plus 5fluorouracil (FEC) followed by pacli taxel. Therefore, our new guideline recommendation is EC without the addition of 5fluorouracil.…”
Section: Adjuvant Cytotoxic and Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on data from the Italian Grupo Italiano Mamella (GIM) study presented by Cognetti et al [76] at the San Antonio Breast Cancer Symposium (SABCS) 2013, epi rubi cin/cyclophosphamide (EC) followed by paclitaxel is equally effective to EC plus 5fluorouracil (FEC) followed by pacli taxel. Therefore, our new guideline recommendation is EC without the addition of 5fluorouracil.…”
Section: Adjuvant Cytotoxic and Targeted Therapymentioning
confidence: 99%
“…For dosedense regimens, additional knowledge has accu mulated in the year 2014: -The Italian GIM study presented by Cognetti et al [76] has shown that EC 90/600 q2w with pegfilgrastim followed by paclitaxel 175 q2w is superior to the same regimen applied at 3weekly intervals. -The NSABP B38 trial published by Swain et al [77] has shown that 6 cycles of TAC is equally effective to dose dense EC followed by paclitaxel q2w.…”
Section: Adjuvant Cytotoxic and Targeted Therapymentioning
confidence: 99%
“…Insbesondere Patientinnen mit estrogenrezeptornegativen (ER-negativen) Tumoren scheinen zu profitieren. Die Wirksamkeit dieses Konzepts ist durch eine zweite Studie bestätigt worden [8]), bei der die Verdichtung der Therapie auf zweiwö-chentliche Zyklen ebenfalls mit einer signifikanten Effektivitätssteigerung im Vergleich zur dreiwöchentlichen Applikation verbunden war. Die Ergebnisse waren unabhängig vom Hormonrezeptorstatus.…”
Section: Rolle Der Dosisintensitätunclassified
“…Cognetti et al [9] gingen mit der GIM-II-Studie den Fragen nach, ob die dosisdichte Therapie (q2w) mittels 4-mal Epirubicin/ Cyclophosphamid gefolgt von 4-mal Paclitaxel der herkömmlichen Gabe (q3w) überlegen ist und ob die zusätzliche Gabe von Fluorouracil einen weiteren Vorteil beim nodal-positiven Mammakarzinom erbringt. Dabei zeigte sich ein hochsignifikanter Vorteil durch die dosisdichte Gabe sowohl für das krankheitsfreie Überleben (19%), als auch für das Gesamtüberleben (32%) der insgesamt 2091 Patientinnen.…”
Section: Lokaleunclassified